2021
DOI: 10.1002/ceat.202000123
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Sulfur Dioxide by Iron(II) Hydroxide Solution in a Multiplate Bubble Column under Magnetic Field

Abstract: In this work, the utilization of iron(II) hydroxide (Fe(OH)2) slurry as the absorbent in wet flue gas desulfurization was investigated. The most important reason for selecting Fe(OH)2 is that iron sulfate, formed by captured sulfur dioxide, can be converted back to Fe(OH)2. First, in the experiments, a bubble column was used with continuous gas and liquid flow. Second, perforated plates were used in the same column. Lastly, a magnetic field was applied to this multiplate bubble column so that the flow of Fe(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Today, a large part of the increasing energy needs due to population growth and developing technology are met by fossil fuels 1 . The harms of greenhouse gases released during the usage of fossil fuels as energy sources to human health and the environment, and the fact that fossil fuel resources will be run out soon, make renewable energy mandatory 2–4 . On the other hand, fossil fuel prices have experienced recent instability, leading oil‐importing countries to explore alternative solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Today, a large part of the increasing energy needs due to population growth and developing technology are met by fossil fuels 1 . The harms of greenhouse gases released during the usage of fossil fuels as energy sources to human health and the environment, and the fact that fossil fuel resources will be run out soon, make renewable energy mandatory 2–4 . On the other hand, fossil fuel prices have experienced recent instability, leading oil‐importing countries to explore alternative solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al 19 used stirring to increase gas−liquid dispersions and mass transfer in the bubble reactor. Yoruk et al 20 added perforated plates to increase the residence time of liquid and allow cross-flow contact between gas and liquid to increase the absorption rate of SO 2 . Im et al 21 reported the introduction of a sieve tray on mass transfer rate and found that a larger hole sieve achieved a better mass transfer rate than a smaller hole sieve due to the breakage of large bubbles without the formation of a gas cap.…”
Section: Introductionmentioning
confidence: 99%